Click, clack, boo - Cronin, Doreen; Lewin, Betsy (New York : Atheneum Books for Young Readers, 2014)
Farmer Brown does not like Halloween, but the animals hold a Halloween party in his barn.
Keywords: Halloween -- Fiction; Domestic animals -- Fiction; Animals -- Fiction